Predictive factors of follow-up non-attendance and mortality among adults with type 2 diabetes mellitus- an analysis of the Malaysian Diabetes Registry 2009 - Chew, Boon How; Lee, Ping Yein; Ghazali, Sazlina Shariff; Cheong, Ai Theng; Ismail, Mastura; Taher, Sri Wahyu (Bentham Science Publishers, 2015)
This study examined the factors associated with follow-up non-attendance (FUNA) and mortality among the adult patients with type 2 diabetes mellitus (T2DM). Data on 57780 T2DM patients from the 2009 diabetes registry were analyzed using multinomial logistic mixed model. Out of 57780 patients, 3140 (5.4%) were lost to follow-up and 203 (0.4%) patients had died. Compared with patients who were under active follow-up, men (OR 1.37), neither on insulin (OR 1.72), nor on antiplatelet agents (OR 1.47), having higher HbA1c (OR 1.15), higher LDL-C (OR 1.18) and complications (OR 1.33) were associated with FUNA. Older age (OR 1.09) and higher LDL-C (OR 2.27) have higher mortality. Across the four different health facilities, medication use (insulin and anti-platelet agents) to achieve better disease control in the younger age when diabetes complication is absent would not cause FUNA and might reduce mortality.